(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
Among the seven solid media, potato dextrose agar (PDA) exhibited the highest radial mycelial growth, with a pH range of 4.5-7.5 being optimal, particularly at pH 6.0 for both growth and sporulation. Richard’s agar also favored significant growth Alternaria alternata causal of alternaria leaf blight of Bael. Temperature trials conducted at 15°C, 20°C, 25°C, 30°C and 35°C revealed that 25°C was the optimal temperature for mycelial growth and sporulation. Significant reductions in growth and sporulation were observed at temperatures below 20°C and above 30°C. These findings provide valuable insights into the ecological preferences of A. alternata, contributing to the development of effective management strategies for Alternaria leaf blight in bael cultivation.